JUSTIFICATION OF THE DESIGN AND PARAMETERS OF THE WHEELS DURING THE DESIGN PROCESS OF THE CHASSIS OF A ROBOTIC PLATFORM USING SOLIDWORKS SIMULATION - KHARZHEVSKYI, Anton; HORIASHCHENKO, Serhiy; KHARZHEVSKYI, Viacheslav (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The design of robotic machines for close reconnaissance of territories is a topical scientific and engineering task, that obviously has a dual purpose – both civilian and military. Despite the fact that leading global companies are engaged in the development of such technical systems, it is important to ensure operation in difficult conditions, in particular in the conditions of the need for increased passability that requires the development of an improved design of wheels and a scientifically based choice of their parameters – which was an aim of the paper. The problem was solved by calculating the strength of the design proposed in the work, that for plastic parts requires to conduct a non-linear static analysis, determination of the forces acting on the wheels in case of its falling from a certain height. It was established that the safety factor is sufficient according to the criterion of maximum normal stresses. The developed new design of wheels for a robotic machine differs from existing designs by an increased diameter and the presence of a tread that significantly increases the passability compared to known prototypes. As a result of the conducted research, it is shown that the cellular structure of the wheel generally increases the strength and rigidity of the wheels. It was also established that despite the increase in the mass of the wheels to ensure the increased passability of the robotic vehicle, the stress value during impact (falling from a height) is reduced due to the proposed rational design of the wheels, while the minimum safety factor according to the criterion of maximum normal stresses is increased. The design is implemented as a computer 3D model and was manufactured using a 3D printer.